Sensory profiles and skin innervation of patients with painful and painless neuropathies. Issue 9 (September 2018) - Üçeyler, Nurcan; Vollert, Jan; Broll, Barbara; Riediger, Nadja; Langjahr, Melissa; Saffer, Nadine; Schubert, Anna-Lena; Siedler, Gabriela; Sommer, Claudia
Abstract : Abstract: We assessed pain characteristics and sensory profiles of a large and extensively phenotyped cohort of patients with polyneuropathies (PNPs) and small fiber neuropathy (SFN) using quantitative sensory testing (QST). Our aim was to detect potentially discriminative QST profiles of patient subgroups determined by pain, etiology, or skin innervation. We prospectively recruited 350 patients with painful and painless PNPs and with SFN at 1 neuromuscular center. After neurological work-up, patients underwent QST at the dorsal foot and 5-mm skin punch biopsy at the lower leg and upper thigh for intraepidermal nerve fiber counts. A healthy control group of 273 volunteers was investigated accordingly. Pain was present in 50% of the patients with PNP with a median intensity of 6/10 on a numeric rating scale, and, by definition, in all patients with SFN, with a median intensity of 5/10 numeric rating scale. Axonal PNP was painful more often than demyelinating PNP ( P < 0.01). Patients with PNP mostly had loss of function profiles, whereas most patients with SFN belonged to the gain of function (hyperalgesia) phenotype. In healthy controls, skin innervation positively correlated with sensory thresholds, whereas this correlation was lost in patients with PNP and SFN. Quantitative sensory testing did not distinguish between painful and painless neuropathies regarding small fiber function, but revealed higher mechanical pain ( P < 0.01) and detection thresholds ( P < 0.05) and lower mechanical pain sensitivity in the group of patients with painful neuropathies. Etiological neuropathy subgroups were not distinguished by QST. Abstract : Neuropathies may be painful and associated with severe sensory deficits. We provide sensory profiles of a large cohort of patients with painful and painless neuropathies as assessed with quantitative sensory testing.